Performance Analysis of Fiber Optic Communication Systems Using Space Division Multiplexing - Gammachu, Namara (ASTU, 2022)
Space division multiplexing is a multiplexing technique used for guided and unguided media, to transmit large amounts of data and highly improve the data-carrying capacity. Space division multiplexing in fiber optic is used to enhance high-capacity information transmission. The capacity of fiber-optic communication technology has increased highly and optical communication technology has been mostly advancing. The current multiplexing techniques like time-division multiplexing, and dense wavelength division multiplexing by using a single mode fiber /Single core fiber. Using these techniques did not overcome over 100 terabits per second per fiber because of the linearity and nonlinearities of fiber optics. To transmit a high capacity over 100 Tbps /fiber and long-haul transmission, the multiplexing techniques that are needed to break the bottleneck of the capacity limit are termed space-division multiplexing. In this thesis work, the materials we used are Matlab and optisystem software. The methods used for doing this work are studying the basic theory, architectures, and related areas of the research, revising this to add the literature, related to fiber optic communication systems with Space division multiplexing, and identifying parameters. The capacity enhancement in fiber space-division multiplexing is 14.75 Pb/s/fiber and thus the haul of transmission is 250km with usable wavelength-band C+L band. The signal/noise ratio is 35 dB with the number of mode one and the number core is four. In fiber-optic communication systems, the fiber loss is 0.2 dB/km with a power consumption reduction is 20 dBm and cross-talk, loss, and distortion reduction in fiber optic using multimode fiber and multicore fiber. The space division multiplexing includes a great role in fiber optics just in case of effective information transmission by enhancing capacity, reduction of unwanted signal, and power during information transmission; space-division multiplexing in fiber optic is incredibly essential for effective communication with extremely high capacity and long haul transmission. Using mode/core or division multiplexing in fiber optic communication to provide a good communication system for future work
Keywords: Space Division Multiplexing, Single-mode fiber, Multicore fiber, capacity enhancement, long-haul transmission, loss reduction, optical communication system